The outcome of the seminal fluid parameters collected via coitus interruptus versus masturbation - Mustafa, Kamarul Bahyah; Zainuddin, Ahmad Murad; I, Ghazali,; Ramli, Roszaman; Abd. Wahab, Noraziana; Awang, Mokhtar; M H, Omar (Malaysian Medical Associations, 2010)
A one year study was carried out to determine the outcome of the seminal fluid parameters collected via masturbation and coitus interruptus in 151 patients who were undergoing intrauterine insemination (IUI) and patients who came for seminal analysis. There were no statistically significant differences in terms of volume, concentration, progressive motility and normal morphology from specimens collected via coitus interruptus compared to specimens collected via masturbation. Pregnancy outcomes were also comparable